Combination of fluorescent and spin labels: a powerful method for the optimization of hydrophilic membranes for the separation of oil-in-water emulsions - Rita S. Alqubelat; Alena D. Kuznetsova; Denis O. Antonov; Maxim A. Mironov (Chimica Techno Acta)
A new method for assessing the quality of fibre coating based on a combination of fluorescence microscopy and electron paramagnetic resonance is presented in this work. An influence of the carboxymethylcellulose/polyvinylamine gel preparation method on the mobility of the spin label was established. The mobility of the spin label changes from 3.5 ns in the case of a polyvinylamine solution to 12.8 ns in the case of a cross-linked gel on the surface of the glass fibre. A qualitative relationship was found between the mobility of the spin label in the gel applied to the glass fibre and the rate of spreading of crude oil over its surface. This method can be used to make membranes for the separation of water-in-oil emulsions.